Validation of analytical model of vehicle brake system. (21st September 2004) - Guner, R.; Yavuz, N.; Kopmaz, O.; Ozturk, F.; , I. Korkmaz
The present paper aims to contribute to dynamic and thermal analysis of the braking phenomenon. To this end, a dynamic model has been established. Using this model, the equation of motion of a car has been derived for straight line braking. In this context, firstly, the pressure variations in the brake hydraulic circuit versus pedal force have been determined. Afterwards, the expressions for friction torques and associated braking forces induced by hydraulic pressure have been taken into account, and substituted into the equation of motion of vehicle. In its last form, this equation has been numerically solved by means of the Newmark integration scheme; so, the distance travelled by car until stopping, along with its speed and deceleration, has been computed. Finally, a thermal analysis in the brake discs and drum has been carried out. An excellent agreement between numerical and test results has been observed. In addition, optimal pressure values for which the rear tyres do not go to lockup have been obtained.